Assessment of the e-readiness of small and medium sized enterprises in the ICT sector in Botswana, with special reference to information access (2009)
D.Litt. et Phil. === The purpose of this research was to determine the status of e-readiness of Small and Medium-Sized enterprises (SMEs) in the ICT sector in Botswana with respect to information access using ICTs for competitiveness in the local and international markets. The population of study consisted of key informants from 114 SMEs in the ICT sector in Gaborone and Francistown, the capital city and the second largest city of Botswana respectively. The official list of ICT companies provided by the government of Botswana was used as the sampling frame. The research used a two-phase design - the preliminary survey and the main survey of the project. The preliminary survey consisted of two stages. During the first stage, a short structured questionnaire was administered to a census of 114 key informants from SMEs in the ICT sector. During the second stage, six focus group discussions were used to collect data from key stakeholders in the ICT sector who included representatives from: ICT companies, ICT professional body in Botswana, government utility corporations, academia and the business community. The participants in the focus group discussions involved representatives from 55 SMEs who were identified like in the first stage using the government official list of SMEs in Botswana. The quantitative data collected through questionnaire were analysed using SPSS while the qualitative data collected through focus group discussions and in-depth interviews were analysed using thematic tables. The results were represented using tables, pie charts, categories and narrations. The results of the preliminary survey of the project were used to characterise the ICT sector in terms of its size, key players, nature of businesses, products and services traded in, distribution of business by location and the issues that affected the sector. This characterisation was important in two main respects. Firstly, it provided a clear roadmap for the design of the main survey of the research since little information existed on the subject of e-readiness on Botswana in general and with respect to SMEs in particular. Similarly, the government had invested a lot of resources in ICT infrastructure development and was focusing on SMEs especially those in the ICT sector to diversify the economy from the dominant diamond mining to service industry. Secondly, the results of the preliminary survey of the project supported the development of a structured interview schedule that was used during the main survey of the project. During the main survey of the research data was collected from companies that participated in the focus group discussions. From the focus group list of participants, an alphabetical name list of 55 SMEs was created. There were 43 Small-Sized and 12 Medium-Sized enterprises that were represented during the focus group discussions. For the purpose of carrying out the structured interviews, SMEs were stratified into two (Small-Sized enterprises and Medium-Sized enterprises). From the Small-Sized enterprises stratum, 20 companies were systematically selected (from the 43) taking every other member on the list. On the other hand, in the Medium-Sized enterprises stratum, all the 12 enterprises were selected for interviews because the number of respondents was small. The data collected was analysed using categories and thematic tables because it was largely qualitative. The results were presented in the form of thematic tables and through narrations. The findings from the SMEs surveyed indicated that most of the SMEs in the ICT sector in Botswana were Small-Sized enterprises that were largely not e-ready to participate in the global electronic business environment because of several impediments such as: the lack of awareness, inadequate policy and legislative framework, poor telecommunication and electricity infrastructures, poor e-commerce infrastructure, inadequate government support, the lack of access to credit, investment barriers, the lack of critical ICT skills and more. The major outcomes of the project include an exposition of the e-readiness status of SMEs in the ICT sector in Botswana, a road map that can assist the government of Botswana to establish a strong export-oriented ICT sector. The weaknesses and strengths of Botswana’s e-readiness status with regard to SMEs are brought to the fore, thus creating awareness upon which the government can design interventions that are tailored to meet Botswana’s SMEs’ specific needs. Similarly, this project provides a framework upon which the government can benchmark against its counterparts in the rest of the world in order to define its investment priorities. The project also provides baseline information which the government could use to implement appropriate policy and legislative decisions in order to enhance the e-readiness of SMEs in the ICT sector in Botswana. Finally, the new integrated e-readiness tool that was developed in this project is the first of its kind to bring the different major components of e-readiness (such as enterprise, ICT, human resources, information and external environment readiness) into a single assessment tool with great attention paid to information access. The tool is also modular in design and thus can allow specific e-readiness assessment of individual segments of society to be modelled independently of each other. The tool also enriches the qualitative aspects of e-readiness that are only minimally addressed in a few of the existing macro e-readiness assessment tools. Among the key recommendations from the research is the need for the government of Botswana to promulgate relevant policies and implement pragmatic programmes that would enable SMEs in the ICT sector in the country to use various information technologies in order to gain access to relevant information regarding access to credit, investment opportunities, partnerships, education and training opportunities so that they can effectively participate in both the local and international markets. The policy changes and programmes to be undertaken by the government should be underpinned by an effective legislative and regulatory framework that would enable the small business firms to identify, acquire, process, organise, disseminate and apply information for competitive advantage through the effective deployment and application of ICTs.